The Current State of Fat Grafting: A Review of Harvesting, Processing, and Injection Techniques. Issue 4 (October 2015) - Strong, Amy L.; Cederna, Paul S.; Rubin, J. Peter; Coleman, Sydney R.; Levi, Benjamin
Abstract : Background: Interest in and acceptance of autologous fat grafting for use in contour abnormalities, breast reconstruction, and cosmetic procedures have increased. However, there are many procedural variations that alter the effectiveness of the procedure and may account for the unpredictable resorption rates observed. Methods: The authors highlighted studies investigating the effects of harvesting procedures, processing techniques, and reinjection methods on the survival of fat grafts. This review focused on the impact different techniques have on outcomes observed in the following: in vitro analyses, in vivo animal experiments, and human studies. Results: This systemic review revealed the current state of the literature. There was no significant difference in the outcomes of grafted fat obtained from different donor sites, different donor-site preparations, harvest technique, fat harvesting cannula size, or centrifugation speed, when tumescent solution was used. Gauze rolling was found to enhance the volume of grafted fat, and no significant difference in retention was observed following centrifugation, filtration, or sedimentation in animal experiments. In contrast, clinical studies in patients found more favorable outcomes with fat processed by centrifugation compared with sedimentation. In addition, higher retention was observed with slower reinjection speed and when introduced into less mobile areas. Conclusions: There has been a substantial increase in research interest to identify methodologies for optimizing fat graft survival. Despite some differences in harvest and implantation technique in the laboratory, these findings have not translated into a universal protocol for fat grafting. Therefore, additional human studies are necessary to aid in the development of a universal protocol for clinical practice.